Geological setting and lithostratigraphy of Bandipur-Gondrang area of Lesser Himalaya, central Nepal - Paudyal, KR; Adhikari, LB; Maharjan, N; Paudel, LP (Bulletin of the Department of Geology, 2013)
Detailed geological mapping was carried out in the Bandipur-Gondrang area of Tanahun district to clarify the geological set up and stratigraphy of the area. Wherever possible, geological mapping is based on stratigraphic units proposed by Stocklin and Bhattarai (1977) in central Nepal and the present mapping is the west ward continuation from Mugling-Banspani area (Paudyal and Paudel, 2011). The study area comprises low grade metasedimentary rocks of Nawakot Complex. The rock succession of the area are divided into six formations as the Kunchha Formation, the Fagfog Quartzite, the Dandagaon Phyllite, the Nourpul Formation with four members, the Dhading Dolomite and the Benighat Slates in stratigraphic upwards. The former four formations belong to Upper Nawakot Group and the remaining one belongs to the Lower Nawakot Group of Nawakot Complex (Stöcklin and Bhattarai, 1977). Based on lithology, the Nourpul Formation is divided into the Purebensi Quartzite, the Amdanda Phyllite, the Labdi Khola Member and the Bandipur Slate from bottom to top respectively. The Purebensi Quartzite is lithologically distinct in the field; the Labdi Khola Member is significant with copper and iron mineralization in the area, and the Bandipur Slate is also significant with roofing quality slate, however, the Amdanda Phyllite is mapped as an intervening member between significant lithologies. The rocks of the present study area consist of several sedimentary structures like mud cracks, ripple marks, graded bedding and cross and parallel laminations. A broad Ghumaune- Gondran Synclinorium is mapped in the area. In addition to this, several anticlines and synclines are also mapped in the study area. Jalbhanjyang Thrust has brought the older metasedimentary rocks of the Nawakot Complex over the younger rocks of the same Complex. Some corrections are recommended over the distribution of previously shown lithological units by Stocklin and Bhattarai (1977) around the Ghumaune-Bhut Khola section. DOI: http://dx.doi.org/10.3126/bdg.v15i0.7417 Bulletin of the Department of Geology, Vol. 15, 2012, pp. 49-62